2020
DOI: 10.1177/2055116919896111
|View full text |Cite
|
Sign up to set email alerts
|

CT-guided drainage of a brainstem abscess in a cat as an emergency treatment procedure

Abstract: Case summary A 3-year-old male neutered domestic shorthair cat was presented with a 1-week progressive and rapidly deteriorating history of lethargy and abnormal behaviour. Neurolocalisation indicated multifocal intracranial lesions (right oculomotor nerve, brainstem [obtundation, non-ambulatory tetraparesis, vestibular dysfunction and intermittent decerebrate rigidity] and possibly the thalamus [left-sided pleurothotonus]), or more likely a single brainstem lesion with mass effect. MRI of the brain demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…[24][25][26] Since the two diseases require very different treatment and have a different prognosis, a correct imaging interpretation is paramount. 13,17,27,28 The aims of the current study were to compare the MRI features of confirmed ring-enhancing gliomas and intra-axial brain abscesses in dogs and cats and to identify the imaging features that might help to differentiate them. The authors' hypotheses were that (1) some MRI qualitative characteristics would be associated with brain abscess/glioma classification and (2) a threshold value for the ratio between lesion diameter and capsule thickness in T1W postcontrast sequences could be used as a cutoff for discriminating between brain abscesses and gliomas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26] Since the two diseases require very different treatment and have a different prognosis, a correct imaging interpretation is paramount. 13,17,27,28 The aims of the current study were to compare the MRI features of confirmed ring-enhancing gliomas and intra-axial brain abscesses in dogs and cats and to identify the imaging features that might help to differentiate them. The authors' hypotheses were that (1) some MRI qualitative characteristics would be associated with brain abscess/glioma classification and (2) a threshold value for the ratio between lesion diameter and capsule thickness in T1W postcontrast sequences could be used as a cutoff for discriminating between brain abscesses and gliomas.…”
Section: Introductionmentioning
confidence: 99%
“…However, overlapping imaging features have been reported 24–26 . Since the two diseases require very different treatment and have a different prognosis, a correct imaging interpretation is paramount 13,17,27,28 …”
Section: Introductionmentioning
confidence: 99%
“…A diagnosis of BM was considered to include (1) the presence of intracellular bacteria on CSF cytological evaluation or (2) positive CSF bacteriological culture or (3) neutrophilic pleocytosis (specifically degenerate neutrophils) on CSF cytological evaluation with clinical improvement after initiation of administration of antibiotics, or these findings in combination. Cases were excluded if they had incomplete medical records or imaging findings consistent with empyema (evidence of accumulation of T1W‐hypointense, T2W‐ and FLAIR‐hyperintense extra‐axial material with peripheral heterogenous contrast enhancement) 10,12 or suspected intracranial abscess formation indicated by a well demarcated mass lesion with a T1W‐hypointense, T2W‐hyperintense center, and strongly contrast enhancing rim 24 …”
Section: Methodsmentioning
confidence: 99%
“…The use of CT-guidance to obtain diagnostic samples from lesions was first described in 1994 in veterinary medicine [2,3]. Since then, several studies have been published in small animals using both stereotactic free-hand CT-guided techniques and CT-guidance devices [4][5][6][7][8][9][10][11][12]. Computed tomographic-guidance provides advantages in comparison to ultrasound-guided techniques, which are the most common sampling techniques in veterinary medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, sampling under CT-guidance is especially indicated for inaccessible or hardly accessible lesions under ultrasound-guidance, like intrathoracic lesions, intracranial lesions and vertebral and paravertebral lesions. There are several studies of CT-guided sampling of intrathoracic lesions [4][5][6], brain lesions [8][9][10]12] and bone lesions too [7].…”
Section: Introductionmentioning
confidence: 99%